Preparing Preservice Teachers to Help Elementary Students Develop Persuasive Science Writing - Croce, Keri-Anne; Spence, Lucy (Innovations in Science Teacher Education, 2023)
To inspire change in the world, scientists must be agile communicators who can persuade different audiences around the globe. Persuasive science writing must reflect an understanding of how culture and language influence audiences in different ways. Examples of scientific writing designed for different audiences around the globe include pamphlets describing safe masking practices or public-service announcements about climate change. Preservice teachers must prepare the next generations of scientists to think of science content in conjunction with communication. This has created a high demand for university programs to prepare preservice teachers to teach elementary students how to create persuasive science writing. The International Science Text Analysis Protocols (ISTAP) teaching methodology was designed to help preservice teachers guide elementary students to develop tools for creating persuasive science writing. This article details how university programs may use ISTAP to support preservice teachers before, during, and after school placements. As linguistic and cultural diversity within science classrooms in the United States continues to expand, students will bring diverse resources into conversations centering on persuasive science writing. As university faculty guide preservice teachers through ISTAP, they are emphasizing diversity within science classrooms and supporting equity within STEM.